Struktur Batin Puisi Bertema Cinta Karya W.S. Rendra dan Ardiansyah - Ansyor Ansyor; Agung Nugroho (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2020)
The purpose of this study was to analyze the love-themed poetry of W. S. Rendra and Ardiansyah. The research method used is a qualitative method based on content analysis. The results of this study indicate that the elements that stand out in the concept of aesthetic development in the love-themed inner structure poetry. Poets are free to play words in order to beautify the poetry of poetry. The inner structure used is the inner structure of the theme, taste, tone and message. In conclusion, the four love-themed poems by W.S. Rendra and Ardiansyah have 52 quotes, including: 15 quotes containing concern and heartbreak, 14 quotes, while the tone and message are 13 and 10 quotes. Keywords: Rhymes Inner Structure